Effect of Electrolyte Concentration on the Stern Layer Thickness at a Charged Interface. (15th February 2016) - Brown, Matthew A.; Goel, Alok; Abbas, Zareen
Abstract: The chemistry and physics of charged interfaces is regulated by the structure of the electrical double layer (EDL). Herein we quantify the average thickness of the Stern layer at the silica (SiO2 ) nanoparticle/aqueous electrolyte interface as a function of NaCl concentration following direct measurement of the nanoparticles' surface potential by X‐ray photoelectron spectroscopy (XPS). We find the Stern layer compresses (becomes thinner) as the electrolyte concentration is increased. This finding provides a simple and intuitive picture of the EDL that explains the concurrent increase in surface charge density, but decrease in surface and zeta potentials, as the electrolyte concentration is increased.